Acculturation of Islamic Culture and Compo Sampari Tradition in Bima Regency, West Nusa Tenggara - Nurul Fauziah; Abdul Habi; Syatriadin Syatriadin (JURNAL PENDIDIKAN IPS, 2025)
This research analyzes the acculturation of Islamic culture with the local Compo Sampari tradition in Nata Village, Palibelo District, Bima Regency, West Nusa Tenggara (NTB). The Compo Sampari tradition is a traditional ceremony that has long been carried out by local people as part of their cultural identity. Meanwhile, the arrival of Islam into the Bima region has brought significant changes in various aspects of social, cultural and religious life. This research uses a qualitative approach with analytical descriptive methods that prioritize in-depth interviews, field observations and documentation studies. The research results show that cultural acculturation between Islam and the Compo Sampari tradition occurs through a process of harmonious interaction. Although Compo Sampari has strong cultural roots in traditional religion and beliefs, elements of Islamic teachings, especially in terms of prayers, procedures for implementation, and social values have been included in the ritual. For example, the use of Islamic prayer phrases in a series of Compo Sampari processions marks the combination of aspects of Islamic spirituality with local traditions. This tradition is not only a means of maintaining cultural values, but also a means of strengthening relations between citizens in Islamic society.